Kualitas Audit Didasarkan Pada Isu-Isu Keahlian Dan Profesionalisme Auditor - Mohammad Ali Sartono (Manajerial, 2015)
This research will examine the views from stakeholders on the quality of audits based on issues of expertise and professionalism of auditors, audits commercialization  and transparency the audit. This study focuses attention on the response from implementation of audits quality regulations according to the company’s audits, the audit committee and investors. The focus of this research is an analysis of research by identifying four major drivers of audit quality, namely: culture in an audit firm; skills and personal qualities of audit partners and staff; the effectiveness of the audit process; the reliability and usefulness of audit reporting. In this study also identifies a number of factors that affect the quality of audit beyond the control of the auditor, namely: the approach taken by management; the contribution made by the audit committee; role of shareholders and commentators; role as a driver of audit quality litigation; regulatory approaches; the pressure caused by the acceleration reports. The results showed that the regulatory bodies and professionals involved in the management and improvement of audit quality to make efforts to improve the tarnished image, increase its legitimacy and reputation as well as the dominance of responses raised concerns about potential damage to the profession.